Statin therapy reduces plasma endothelin-1 concentrations: A meta-analysis of 15 randomized controlled trials - Sahebkar, Amirhossein; Kotani, Kazuhiko; Serban, Corina; Ursoniu, Sorin; Mikhailidis, Dimitri P.; Jones, Steven R.; Ray, Kausik K.; Blaha, Michael J.; Rysz, Jacek; Toth, Peter P.; Muntner, Paul; Lip, Gregory Y.H.; et al. (Atherosclerosis, 2015)
Raised plasma endothelin-1 (ET-1) levels may be a risk factor for vascular dysfunction and cardiovascular (CV) disease. This meta-analysis assessed the effect of statins on circulating ET-1 concentrations. The search included PUBMED, Cochrane Library, Web of Science, Scopus, and EMBASE up to September 30, 2014 to identify randomized controlled trials (RCTs) with ET-1 measurement during statin therapy. Quantitative data synthesis was performed using a random-effects model, with weighed mean difference (WMD) and 95% confidence interval (CI) as summary statistics. Data from 15 RCTs showed that statin therapy significantly reduces plasma ET-1 concentrations (WMD: −0.30 pg/mL, 95%CI: −0.47, −0.13; p < 0.01). This effect was robust in sensitivity analysis, and not largely affected by the duration of statin therapy (<12 weeks – WMD: −0.51 pg/mL, 95%CI: −0.89, −0.14, p < 0.01; >12 week –WMD: −0.19 pg/mL, 95%CI: −0.36, −0.02; p < 0.05) or by dose of statins (<40 mg/day – WMD: −0.27 pg/mL, 95%CI: −0.49, −0.05; p = 0.01; >40 mg/day – WMD: −0.38 pg/mL, 95%CI: −0.68, −0.08; p = 0.01). Lipophilic (atorvastatin, simvastatin, fluvastatin, and cerivastatin – WMD: −0.34 pg/mL, 95%CI: −0.55, −0.13; p < 0.01), but not a hydrophilic statin (pravastatin – WMD: −0.18 pg/mL, 95%CI: −0.44 −0.08; p > 0.05) had a significant effect in promoting ET-1 reduction. Statin therapy significantly reduces circulating ET-1 concentrations, regardless of treatment duration or dose of statins. This effect of statins may be influenced by statin lipophilicity. There is a need to establish whether lowering ET-1 levels has a beneficial effect on CV events. •Raised ET-1 levels may be a risk factor for vascular dysfunction and CVD.•We showed that statin therapy significantly reduces ET-1 (−0.30 pg/mL).•Lipophilic, but not a hydrophilic statin had a significant effect on ET-1 reduction.•We need to establish whether lowering ET-1 has a beneficial effect on CV events.